Community-based HPV self-collection versus visual inspection with acetic acid in Uganda: a cost-effectiveness analysis of the ASPIRE trial. Issue 6 (12th June 2018) - Mezei, Alex K; Pedersen, Heather N; Sy, Stephen; Regan, Catherine; Mitchell-Foster, Sheona M; Byamugisha, Josaphat; Sekikubo, Musa; Armstrong, Heather; Rawat, Angeli; Singer, Joel; Ogilvie, Gina S; Kim, Jane J; et al.
Abstract : Background: Cervical cancer is the leading cause of cancer death for women in Uganda, despite the potential for prevention through organised screening. Community-based self-collected human papillomavirus (HPV) testing has been proposed to reduce barriers to screening. Objective: Our objective was to evaluate the cost-effectiveness of the Advances in Screening and Prevention of Reproductive Cancers (ASPIRE) trial, conducted in Kisenyi, Uganda in April 2014 (n=500). The trial compared screening uptake and compliance with follow-up in two arms: (1) community-based (ie, home or workplace) self-collected HPV testing (facilitated by community health workers) with clinic-based visual inspection with acetic acid (VIA) triage of HPV-positive women ('HPV-VIA') and (2) clinic-based VIA ('VIA'). In both arms, VIA was performed at the local health unit by midwives with VIA-positive women receiving immediate treatment with cryotherapy. Design: We informed a Monte Carlo simulation model of HPV infection and cervical cancer with screening uptake, compliance and retrospective cost data from the ASPIRE trial; additional cost, test performance and treatment effectiveness data were drawn from observational studies. The model was used to assess the cost-effectiveness of each arm of ASPIRE, as well as an HPV screen-and-treat strategy ('HPV-ST') involving community-based self-collected HPV testing followed by treatment for all HPV-positive women at the clinic. Outcome measures: The primary outcomes were reductions in cervical cancer risk and incremental cost-effectiveness ratios (ICERs), expressed in dollars per year of life saved (YLS). Results: HPV-ST was the most effective and cost-effective screening strategy, reducing the lifetime absolute risk of cervical cancer from 4.2% (range: 3.8%–4.7%) to 3.5% (range: 3.2%–4%), 2.8% (range: 2.4%–3.1%) and 2.4% (range: 2.1%–2.7%) with ICERs of US$130 (US$110–US$150) per YLS, US$240 (US$210–US$280) per YLS, and US$470 (US$410–US$550) per YLS when performed one, three and five times per lifetime, respectively. Findings were robust across sensitivity analyses, unless HPV costs were more than quadrupled. Conclusions: Community-based self-collected HPV testing followed by treatment for HPV-positive women has the potential to be an effective and cost-effective screening strategy.